Strength Analysis for Motor Car Body of Power Centralized EMU - Xiangtao LI; Caiying MI (机车电传动)
The car body structural strength of power concentrated EMU was analyzed, and the finite element model was established by using HyperMesh12.0 software. According to the standard of UIC 566 and EN 12663-1/2010 to determine the body's static strength load conditions and fatigue strength load conditions, static strength of the car body based on von Mises stress was assessed; The fatigue strength of the vehicle body was evaluated according to the fatigue strength method of welded steel structure based on DVS 1612 standard; By using Block Lanczos method in ANSYS software, the situation of the body stiffness was assessed with the free mode analysis of body structure without the top. Through the calculation and analysis of the car body model, the design of the car body structure of power concentrated EMU met the relevant requirements of strength and stiffness.